Deep Brain Stimulation and Cognitive Decline in Parkinson’s Disease: A Clinical Review - Massano, João; Garrett, Carolina (Frontiers in Neurology, 2012)
Parkinson’s disease (PD) is a common and often debilitating disorder, with a growing prevalence accompanying global population aging. Current drug therapy is not satisfactory enough for many patients, especially after a few years of symptom progression. This is mainly due to the motor complications that frequently emerge as disease progresses. Deep brain stimulation (DBS) is a useful therapeutic option in carefully selected patients that significantly improves motor symptoms, functional status and quality of life. However, cognitive impairment may limit patient selection for DBS, as patients need to have sufficient mental capabilities in order to understand the procedure, as well as its benefits and limitations, and cooperate with the medical team throughout the process of selection, surgery and postsurgical follow up. On the other hand it has been observed that certain aspects of cognitive performance may decline after DBS, namely when the therapeutic target is the widely used subthalamic nucleus. These are important pieces of information for patients, their families and health care professionals. This manuscript reviews these aspects and their clinical implications.